El cultivo de la espinaca (Spinacia oleracea L.) y su manejo fitosanitario en Colombia - Gil, Rodrigo; Fuentes, Luz S.; Espinosa, Ligia; Arias, Luis A.; Rodríguez, Marcela; Garzón, Catlina; Jiménez, Jaime (UJTL, 2018)
Espinaca-Spinacia oleracea